EVALUASI PELAYANAN VAKSIN COVID – 19 (STUDI KASUS PUSKESMAS MOJO KOTA SURABAYA) - Maharani Ulya Fadhilah; Umi Fauziyah; Adellia Ammertia Cahyani; Lukman Arif (Universitas Halu Oleo, 2021)
During the COVID-19 pandemic, cases of the increase in positive patients in Indonesia were getting out of control and increasing in number, therefore the Government is ready for a vaccine that will be given in stages according to the priority of the recipient as an effort to tackle the spread of COVID-19 transmission. Vaccination can be carried out in health agencies such as in Puskesmas. The purpose of this research was to evaluate the quality of service in the implementation of the COVID-19 vaccination at Puskesmas Mojo Surabaya. The research method used is a qualitative approach with descriptive methods. The data technique used was observation, interview, and documentation study and then analyzed using an interactive data analysis model. The results of this study are the quality of the COVID-19 vaccination service at Puskesmas Mojo Surabaya based on the dimensions of public service Tangibles, Reliability, Responsiveness, Assurance, and Emphaty. Applicable in the process of vaccination services at Puskesmas Mojo Surabaya on complicated online data collection and scheduling, because not all of the facilities and population data are available where there have never been residents who have moved, therefore the result is a long queue to update the data. The quality of vaccine services at Puskesmas Mojo Surabaya is satisfactory in terms of facilities, services, and resources and it is necessary to make efforts to schedule and collect data more regularly to overcome service process constraints